The Mesoproterozoic Nampula Subdomain in southern Malawi: Completing the story from Mozambique. (December 2022) - Thomas, Robert J.; Fullgraf, Thomas; Macey, Paul H.; Boger, Steven D.; Hölttä, Pentti; Lach, Philippe; Le Roux, Petrus; Dombola, Kondwani; Zammit, Carol
Abstract: New field mapping, lithostratigraphic, whole-rock geochemical, U–Pb zircon and radiogenic isotope data on the Nampula Subdomain of southernmost Malawi show good correlation with those published from adjacent NE and NW Mozambique. The oldest rocks, dated between ∼1180 and 1070 Ma form a complexly interlayered sequence of supracrustal layered paragneisses and migmatites (Nampula Group), intimately interlayered with intermediate-basic (Mocuba Suite) and felsic (Mamala Suite) gneisses, likely meta-volcanic and meta-plutonic in origin. The Mocuba Suite has typical calc-alkaline, I-Type granitoid, TTG compositions, with generally positive ϵNd values, NdTdm ages around 1.2 Ga and low initial 87 Sr/ 86 Sr ratios. These characteristics indicate generation in a juvenile volcanic arc setting at this time. Minor exceptions include a few samples which show limited input of Palaeoproterozoic crust. The Nampula arc is viewed as one of a number that developed in a closing oceanic basin which lay between the Archaean-Palaeoproterozoic Congo-Bangweulu-Ubendian-Tanzania cratonic blocks in the north and the Zimbabwe Craton to the SW, and which can be traced "southwards" in Gondwana to continue in the NE part of the ∼1 Ga Maud belt in East Antarctica. The Nampula arc-complex was intruded at ∼1040 by syn-to late tectonic sheets of megacrystic granite/augen gneisses of the Culicui Suite and, at ∼1000 Ma, by a number of bodies of late-to post-tectonic, massif-type anorthosite (Tengani Suite), which are unique to the Malawian segment of the Nampula Subdomain. The anorthosites are considered to have intruded at a post-tectonic stage under a late Mesoproterozoic extensional regime. The rocks underwent deformation and high grade metamorphism in both the Mesoproterozoic (Irumide) and Neoproterozoic-Cambrian (Pan-African) orogenies. P-T data suggest the latter attained peak granulite facies conditions of ∼800 °C at a maximum of 13–18 kbar, comparable with Neoproterozoic granulites in adjacent areas. The data presented here do not rule out either Irumide (∼1 Ga) juxtaposition of the Congo and Kalahari cratons (in Rodinia), or Pan-African (∼0.5 Ga) collision (Gondwana). Instead of this "either-or" situation, a recent hypothesis suggests accretion/collision occurred during both orogenies, separated by a period of drift apart, by the "strange attractor" phenomenon. Our data do not rule exclude that contention; rather, they tend to support it. Highlights: Nampula Subdomain in Malawi equated with neighbouring Mozambique Zircon dates from 8 Mesoproterozoic orthogneisses range from ∼1180 to 1000 Ma Rocks have mostly "juvenile" Sm–Nd isotope signatures WR geochemical suggest arc-like signatures for most igneous rocks Neoproterozoic maximum metamorphic P-T conditions estimated around 800 °C at up to 13–18 kbar